2016
DOI: 10.1088/0957-4484/27/32/325101
|View full text |Cite
|
Sign up to set email alerts
|

Xanthan gum stabilized PEGylated gold nanoparticles for improved delivery of curcumin in cancer

Abstract: In recent years, gold nanoparticles (AuNPs) have received immense interest in various biomedical applications including drug delivery, photothermal ablation of cancer and imaging agent for cancer diagnosis. However, the synthesis of AuNPs poses challenges due to the poor reproducibility and stability of the colloidal system. In the present work, we developed a one step, facile procedure for the synthesis of AuNPs from hydrogen tetrachloroaurate (III) hydrate (HAuCl4. 3H2O) by using ascorbic acid and xanthan gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(18 citation statements)
references
References 49 publications
0
17
1
Order By: Relevance
“…The addition of PEG improved an extended systemic circulation of the polymer, and highlights the ability of producing multicomponent systems with a positive combined action. These nanoparticles had an enhanced cytotoxicity activity against lung cancer cells due to XG’s functional groups [ 83 ].…”
Section: Exopolysaccharides For Producing Ddssmentioning
confidence: 99%
“…The addition of PEG improved an extended systemic circulation of the polymer, and highlights the ability of producing multicomponent systems with a positive combined action. These nanoparticles had an enhanced cytotoxicity activity against lung cancer cells due to XG’s functional groups [ 83 ].…”
Section: Exopolysaccharides For Producing Ddssmentioning
confidence: 99%
“…Another compound, curcumin is a polyphenol found in turmeric has broad pharmacological activities, including anti-inflammatory, anti-oxidative, and anti-tumour effects (31). Also, it has been found that curcumin can reverse drug resistance in tumour cells from gastric, hepatic and cervical cancers as well as other malignancies (32,33).…”
Section: Introductionmentioning
confidence: 99%
“…It exhibits a wide range of pharmacological properties, including anti-inflammatory, anti-angiogenic, anti-oxidative and anticancer effects ( 9 11 ). Previous studies have demonstrated that curcumin reversed MDR in various tumors, including gastric, hepatic, and cervical cancer ( 12 , 13 ). However, the mechanisms associated with the MDR reversal effect of curcumin and its targets remain to be fully elucidated.…”
Section: Introductionmentioning
confidence: 99%